Severe atherosclerosis in the natural mummy of Girolamo Macchi (1648–1734), "major writer" of Santa Maria della Scala Hospital in Siena (Italy). (January 2019) - Gaeta, Raffaele; Fornaciari, Antonio; Izzetti, Rossana; Caramella, Davide; Giuffra, Valentina
Abstract: Background and aims: A small crypt in the Santissima Annunziata Church of Santa Maria della Scala Hospital in Siena (Italy) contained three well-preserved mummies, two of which, dated back to the 15th-16th century, were identified as Salimbene Capacci (1433–1497), Rector of the Hospital, and his wife, Margherita Sozzini (?-1511). The third mummy, dressed in clothes of the 17th century, was not initially identified. Methods: Accurate bibliographical, taphonomic and anthropological studies allowed the identification of the mummy of Girolamo Macchi, who lived between 1648 and 1734 and worked as "major writer", an accountant, for the Hospital. He was present when the corpses of the Rector and his wife were discovered in 1678 and, impressed by this finding, wanted to be buried in the same chapel after his death, which occurred at the age of 86. A complete study, including macroscopic, radiological, isotopic and histological analyses, was performed on the natural mummy of Girolamo. Results: Macroscopic investigation showed a large inguinoscrotal hernia and a good preservation of the internal organs. The circulatory system revealed severe atherosclerosis, with multiple calcifications stenosing the lumen of the vessels, in particular of the lumbar aorta and the iliac arteries. The diagnosis was confirmed by imaging techniques (3D Cone Beam Scan) and by histology. Conclusions: This case confirms that atherosclerosis is also a disease of ancient times. The presence of atherosclerosis in pre-contemporary individuals could suggest that the disease may not only be uniquely characteristic of a specific diet or lifestyle, but it could be also an inherent component of human ageing. Graphical abstract: Highlights: In the crypt of S. Maria della Scala Hospital (Siena, Italy) a 17th century natural mummy was found; it was Girolamo Macchi. A complete study, including macroscopic, radiological, isotopic and histological analyses, was performed on the mummy. The circulatory system, like the lumbar aorta, showed atherosclerosis, with calcifications stenosing the lumen of the vessels. The diagnosis was confirmed by imaging techniques (3D Cone Beam Scan) and by histology. Atherosclerosis in ancient subjects indicates that the disease could be an inherent component of human ageing.